Simple ML Detector for Multiple Antennas Communication System - Taqwa, Ahmad; Soegijoko, Soegijardjo; Sugihartono, Sugihartono; Tjondronegoro, Suhartono (Makara Journal of Technology, 2009)
Simple ML Detector for Multiple Antennas Communication System. In order to support providing broadband wireless communication services against limited and expensive frequency bandwidth, we have to develop a bandwidth efficient system. Therefore, in this paper we propose a closed-loop MIMO (Multiple-Input-Multiple-Output) system using ML (Maximum Likelihood) detector to optimize capacity and to increase system performance. What is especially exciting about the benefits offered by MIMO is that a high capacity and performance can be attained without additional frequency-spectral resource. The grand scenario of this concept is the attained advantages of transformation matrices having capability to allocate transmitted signals power suit to the channel. Furthermore, product of these matrices forms parallel singular channels. Due to zero inter-channels correlation, thus we can design ML detector to increase the system performance. Finally, computer simulations validates that at 0 dB SNR our system can reach optimal capacity up to 1 bps/Hz and SER up to 0.2 higher than opened-loop MIMO.